Analysis of the level of difficulty of questions in assessment tests based on literature review - Syahrani, Syahrani; Arnol, Allya Mecca; Arafa, Cayhan Aditya; Azhara, Fadillah; Silalahi, Andre Liano Putra (Lembaga Riset Mutiara Akbar, 2026)
Analyzing each exam question is a fundamental step in ensuring the quality of assessment instruments used in the instructional process. One crucial parameter in evaluation is the analysis of the level of question difficulty, as this is directly proportional to the accuracy of measuring student learning outcomes. This study aims to provide a comprehensive explanation of the concept of level of difficulty, the procedure for creating quality questions, and the urgency of item evaluation in creating balanced and fair assessments. This study uses a descriptive qualitative approach with a literature study method (library research). Data were obtained from secondary sources including textbooks, journal articles, and various relevant scientific documents, which were then analyzed using content analysis techniques. The results of the study indicate that ideal questions must meet the balance between the level of difficulty (P) and discriminating power (D). Quality questions are not extreme; questions that are too easy will reduce test reliability, while questions that are too difficult can trigger anxiety and despair in students. The conclusion of this study confirms that teachers' understanding of descriptive item statistics—including the effectiveness of distractors—is an absolute requirement for improving educator professionalism in building quality question banks and supporting the objective achievement of learning objectives.